The Effect of B on the Co-Segregation of C-Cr at Grain Boundaries in Austenitic Steels - Xin Yan; Panpan Xu; Peide Han; Nan Dong; Jian Wang; Caili Zhang (Metals, 2023)
In austenitic steels, the co-segregation of C and Cr at grain boundaries can result in the formation of Cr23C6. However, the addition of B to steels can effectively reduce the amount of Cr23C6 formed and inhibit its ripening in experiments, simultaneously transforming it into Cr23(BC)6. Therefore, the effect of B on the co-segregation of C and Cr at the Σ5(210), Σ9(221) and Σ11(113) grain boundaries in austenitic steels was investigated using density functional theory. The results indicate that B, C, and Cr all tend to segregate at the three grain boundaries, with B and C showing a stronger segregation tendency. Furthermore, co-segregation of C and Cr with short distances occurs readily at the Σ5(210), Σ9(221) and Σ11(113) grain boundaries. The presence of B at grain boundaries can impede the segregation of Cr, particularly at the Σ9(221) and Σ11(113) grain boundaries. When B is pre-segregating at the Σ5(210) grain boundary, B, C, and Cr tend to co-segregate at the grain boundary. The grain boundary B hinders the accumulation of Cr near it for most grain boundaries, thereby inhibiting the co-segregation of Cr and C, making it difficult for B, C, and Cr to aggregate at most grain boundaries. This is beneficial for controlling the nucleation of Cr23(BC)6.